1986
DOI: 10.1093/carcin/7.12.2051
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the met oncogene in the human MNNG-HOS cell line involves a chromosomal rearrangement

Abstract: In this study it is demonstrated that the activated met gene, which was originally detected in the MNNG-HOS chemically transformed human cell line, is a chimeric gene formed by the joining together of two distinct regions of DNA. Rearrangement of cellular DNA in MNNG-HOS cells was demonstrated by Southern analyses, which showed that the MNNG-HOS cell line contained unique met-related DNA fragments that were not detected in the parental cell line, HOS. Chromosomal localization using a series of rodent-human hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…It acts as an oncogene in the N-methyl-N'-nitro-N-nitrosoguanidine-(MNNG)-transformed human osteosarcoma (HOS) cell line (231)(232)(233). The MET oncoprotein is the receptor for hepatocyte growth factor/scatter factor (HGF/SF) ligands (213) (see above).…”
Section: Met Mc/msh-r Mitfmentioning
confidence: 99%
“…It acts as an oncogene in the N-methyl-N'-nitro-N-nitrosoguanidine-(MNNG)-transformed human osteosarcoma (HOS) cell line (231)(232)(233). The MET oncoprotein is the receptor for hepatocyte growth factor/scatter factor (HGF/SF) ligands (213) (see above).…”
Section: Met Mc/msh-r Mitfmentioning
confidence: 99%
“…1 (13,14). This chimeric gene is transcribed to produce a unique 5.0-kb hybrid tpr-met mRNA that is in turn translated to form a 60-to 65-kDa fusion protein in which the protein tyrosine kinase domain of met is fused to the amino-terminal region of the trp protein (13,14,29,33).…”
Section: The Met Genementioning
confidence: 99%
“…For example, H-ras is activated in N-methyl-N-nitrosourea (MNU)-induced rat mammary tumors and in dimethylbenz[a]anthracene (DMBA)-initiated mouse skin papillomas and carcinomas, while both N-ras and K-ras are activated in thymomas that arise in MNU-treated RF/AKR mice (7)(8)(9)(10)(11)(12). However, genes that are unrelated to ras are also frequently detected, and in a minority of cases (e.g., for met and neu), the mechanism of gene activation of these non-ras genes has been examined in detail (13)(14)(15)(16). Since the role of ras gene activation in chemical carcinogenesis has been adequately discussed elsewhere (17)(18)(19), this review will deal entirely with the non-ras genes that are activated in chemically induced tumors and chemically transformed cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…16 Two leucine zippers in the Tpr moiety cause constitutive dimerization and sustained activation of the Met kinase domain. 17 The Tpr-Met translocation arose in a human osteosarcoma cell line after treatment with the chemical carcinogen N-methyl-N 0 -nitro-N-nitrosoguanidine (MNNG).…”
mentioning
confidence: 99%
“…17 The Tpr-Met translocation arose in a human osteosarcoma cell line after treatment with the chemical carcinogen N-methyl-N 0 -nitro-N-nitrosoguanidine (MNNG). 16 It has been shown that MNNG causes gastric cancer in monkeys. 18 Although not common in human tumors, Tpr-Met has been reported in gastric carcinomas.…”
mentioning
confidence: 99%